2018
DOI: 10.1002/alr.22247
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 24‐hour surgical cancellations in an academic rhinology and skull base surgery practice

Abstract: Background: Late cancellations within 24 hours of surgery lead to decreased utilization of operating room time with loss of productivity, decreased access to care, and inconvenience to patients and staff. To date, no studies have analyzed 24-hour cancellations in a tertiary rhinology practice. Methods:All procedures performed at a tertiary rhinology/skull base practice from January 2016 to December 2017 were reviewed. Twenty-four-hour cancellations were analyzed by procedure type and reason for cancellation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…As an intervention measure to reduce late cancellation rates, preoperative telephone contact is useful. Avila et al, through preoperative telephone calls, reduced the cancellation rate from 18% to 5.4% [11] while Kaye et al reported a reduction from 26% to 10.8% in surgical suspension due to patient absenteeism [23] . In this study, after the previous telephone call, there was a significant reduction in cancellations due to non-attendance from 16% in 2018 to 8% after telephone contact / 2019.…”
Section: Discussionmentioning
confidence: 99%
“…As an intervention measure to reduce late cancellation rates, preoperative telephone contact is useful. Avila et al, through preoperative telephone calls, reduced the cancellation rate from 18% to 5.4% [11] while Kaye et al reported a reduction from 26% to 10.8% in surgical suspension due to patient absenteeism [23] . In this study, after the previous telephone call, there was a significant reduction in cancellations due to non-attendance from 16% in 2018 to 8% after telephone contact / 2019.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Encountering an unexpected active infection may also result in the need for same day cancellation of an ESBS, which can be very disruptive for the patient, the surgeon, and the health care system. 14 Thus, sinus findings on preoperative imaging in this patient population need to be critically evaluated and can represent a serious threat to successful ESBS.…”
Section: Introductionmentioning
confidence: 99%
“…Same day cancellation rates among different units varies considerably. The 6.1%–30.3% of cancelled operations are cancelled on the day of surgery 2 17 19–22. Reports show that 9%–16% of same-day cancellations are due to patient non-attendance on the day of the operation without any prior warning 14 17 23.…”
Section: Introductionmentioning
confidence: 99%